Sunshine Recoder Camble Stokes Media Training Based on Field Case Method on Atmospheric Material for Mgmp Geography Sma/Ma Teachers Bukittinggi City - Nova, Sari; Chandra, Deded; Mariya, Sri; Edial, Helfia; Pertiwi, Mentari Dian; Putri, Sri Kandi; Jasiro, Affandri; Wilis, Ratna; Iswandi, Iswandi (Sumatra Journal of Disaster, Geography and Geography Education, 2025)
This article aims to improve teachers' skills in developing Campbell Stokes' Sunshine Recorder interactive media and improve teachers' understanding of pedagogical aspects seen in the process of lesson planning and learning media. This activity was carried out in the Meeting Room of SMAN 1 Bukittinggi City by using training, question and answer, and practice methods. The participants of this activity were high school Geography subject teachers in Bukittinggi City. This activity includes training on designing effective learning media and also providing training on developing interactive learning media on the topic of Atmosphere for high school geography teachers in Bukittinggi City. The training carried out with Geography subject teachers aims to improve teacher skills in developing Atmospheric learning media through Campbell Stokes' Sunshine Recorder media. Through this training, teachers experienced an increased understanding of pedagogical aspects, especially in understanding and developing learning media, especially in the use of Sunshine Recorder Campbell Stokes media. Geography teachers also gained a better understanding of the competencies needed to design and use media effectively, so as to create quality, efficient and interactive learning experiences.